NILAI DAN VEKTOR EIGEN MATRIKS INTERVAL ATAS ALJABAR MAX-PLUS - M, Dwi Suci; suryoto., Suryoto (MATEMATIKA, 2009)
An interval matrix A with given and is the set of all matrices such that . Eigenvalue and eigenvector of A is called possible eigenvalue and eigenvector of an interval matrix